Orthodoxy, heterodoxy, and reform: constructing an Islamic universe in the British official mind, 1860-1914 - Meleady, C (2019)
This dissertation concerns conceptualizations of Islam produced by the world of the nineteenth century British colonial official. It argues that, contrary to much of the standard scholarship concerning Western engagement with Islam and Muslims in the age of empire, the British officials who staffed the empire perceived Islam as a religion riven by sectarian division. In order to come to terms with the diversity encountered across their Islamic empire, the ‘official mind’, a reflexive acknowledgement of the importance of the Muslim world in Britain’s imperial project, attempted to bring order to this conceptual chaos by anchoring its understanding of Islam in terms of orthodoxy, heterodoxy, and reform. In the process, the official mind became subject to several contexts, the most important of which were the religious, cultural, and educational background of the officials themselves; the significance of India as the location where the most intimate relationships with Muslims were built; and the influence of native Muslim voices, who in some cases won the ear of their British masters and helped shape colonial policy.